Myology and kinesiology manual for the massage therapists - Moorcroft, Cindy (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
'This book is designed for massage therapy students taking a Myology (study of muscles) and/or Kinesiology (study of movement) course as part of their massage curriculum. Because muscles permit our body's movement, these topics complement each other. Massage therapy is frequently defined as the systematic manipulation of soft tissue of the body for therapeutic purposes'--Provided by publisher.
This book includes online access http://thepoint.lww.com/Moorcroft, please refer to library staff for the password.
Includes bibliographical references and index.
Keywords: Musculoskeletal System -- anatomy & histology; Movement -- physiology; Musculoskeletal Manipulations; Musculoskeletal Physiological Phenomena